Kościół katolicki i życie religijne Polaków w Żytomierzu w latach 1917–1991 - Kobus, Andrzej (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The presented article is devoted to the religious standing of Poles living in Żytomierz in the Soviet Union times. The author discusses the legal status of Roman Catholic parishes in Żytomierz and its nearest neighbourhood after the Bolshevik Revolution in 1917 and later on. Profiles of Żytomierz Catholic priests have been introducted who acted until the Soviet Union collapse in 1991. Furthermore, the author attempts to show the relations that the Żytomierz Poles held with Poland and her structures of the Roman Catholic Church during the USSR era.